Strategi pengembangan destinasi pariwisata kabupaten biak numfor provinsi papua - Rumpaidus, George Alfberth; Putra, Agus Muriawan; Widyatmaja, I Gusti Ngurah (Jurnal Kepariwisataan dan Hospitalitas; Vol 3 No 2 (2019): Vol.3,No.2,2019, 2019)
ABSTRACT Diversity objects and tourist attraction in Biak Numfor Regency was veriety attraction nature coast , history and culture . Facilities include accommodation tourism , transport and communication good enough so Biak Numfor Regency for worth developed as tourist destinations . Research aims to identify objects and tourist attraction, internal and external constraints faced,  and analyze internal and external factors of tourism development in Biak Numfor Regency Papua Province. Methods used in this study consisting of observation, interview, kuisioner, literature and documentation. Analyzed resources by method descriptive qualitative, IFAS-EFAS analysis, internal-eksternal analysis ( i-e ) and SWOT analysis. Based on analysis of the internal (strength and weakness)  note that position objects and tourist attraction in Biak Numfor Regency be in the strong or potentially to be developed. According to the analysis of external (opportunities and threats) position objects and tourist attraction Biak Numfor Regency good or have a chance to thrive. Strategies to arrages development programs include forming programs of block plan tourism area, object inventory and tourist attraction programs, promotion development programs, accommodation development programs, public relations programs, environmental security improvement programs, institutional formation programs, HR improvement programs, tourism awareness counseling program. Was recommended to Tourism Departmen of Biak Numfor Regency to be more socialization, training and approach cultural to build a good understanding of the local people on the management tourism as well as, and build good partnership for all stakeholders tourism and Forming an institution regional tourism promotion of Biak Numfor Regency, so that led to the development of tourism into a better. Keywords: development strategy, tourism, objects and tourist attraction.